THE INFLUENCE OF COACHING STRATEGIES, MOTIVATION, AND COMMUNICATION OF COACHES ON THE PRODUCTIVITY OF SMALL STAR BASKETBALL CLUB ATHLETES - Jesica Febiananta; Defrizal Defrizal (ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the influence of training strategies, athlete motivation, and coach communication on the productivity of Small Star Basketball Club athletes in Bandar Lampung City. The research uses a quantitative approach with an associative design. The population as well as the sample consisted of 30 active athletes in the age group of 15 years old with saturated sampling techniques. Data were collected through a five-level Likert scale questionnaire as well as documentation and literature studies. Data analysis was carried out using SPSS through validity, reliability, classical assumption test, and multiple linear regression with t-test, F test, and determination coefficient. The results of the study showed that training strategies and motivation had a positive and significant effect on athlete productivity, while coach communication had a significant negative effect. Simultaneously, these three variables have a significant effect on athlete productivity, which emphasizes the importance of synergy between technical, motivational, and communication aspects in coaching basketball athletes.